Multidimensional Analysis of Risk Factors for Stunting in Rural South Sumatra, Indonesia: A Community-Based Study - Hidayat, Rachmat (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Stunting remains a pressing public health concern in Indonesia, particularly in rural areas. This study aimed to comprehensively analyze the multidimensional risk factors associated with stunting in rural South Sumatra, considering socio-demographic, maternal, and child-related factors. Methods: A community-based cross-sectional study was conducted in rural villages of South Sumatra. Children aged 6-59 months were enrolled, and data on socio-demographic characteristics, maternal health, child feeding practices, and anthropometric measurements were collected. Stunting was defined as height-for-age Z-score <-2SD according to the WHO growth standards. Multivariable logistic regression was employed to identify independent risk factors for stunting. Results: A total of 520 children were included in the study. The prevalence of stunting was 32.5%. In the multivariable analysis, factors significantly associated with stunting included low maternal education (OR: 2.87, 95% CI: 1.72-4.78), poor household wealth index (OR: 3.12, 95% CI: 1.95-4.97), inadequate dietary diversity (OR: 2.45, 95% CI: 1.53-3.92), and suboptimal breastfeeding practices (OR: 2.01, 95% CI: 1.25-3.23). Conclusion: This study highlights the multidimensional nature of stunting risk factors in rural South Sumatra. Interventions addressing maternal education, poverty alleviation, improved child feeding practices, and breastfeeding promotion are crucial to effectively combat stunting in this region.